Vivência transicional da pessoa com acidente vascular cerebral isquêmico tratada por trombolítico - Biasuz, Sandra (2024)
Stroke (STROKE) is one of the main causes of mortality worldwide, resulting in neurological, motor and cognitive sequelae, and represents a serious public health problem. Stroke survivors face a process of adaptation to daily life, characterized by diversity, complexity and multiple dimensions. The study aimed to understand the transition process of people who experienced the occurrence of an ischemic stroke (I-STROKE), who received thrombolytic treatment. The research was conducted in a reference hospital for I-STROKE, using a qualitative approach. Data collection took place between January and November 2023. Following the established criteria, a total of 13 people were eligible to participate. In the first interview, at the time of hospital discharge, the Rankin scale, the Mini Mental State Examination (MMSE), and the National Institute of Health Stroke Scale (NIHSS) were applied. The second stage of the collection occurred in the household within 90 days after stroke-I. The interview, recorded, was conducted with use of semi-structured script, with sociodemographic data, clinical and landmark questions related to the subject under investigation, prepared by the researcher. Subsequently they were transcribed in full, the evaluation of the data was guided by the analysis of thematic content of the operative proposal and the discussion supported by the Meleis' Transition Theory. Of the participants in the study, 70% were female with an average age of 62 years. The lowest score of the MMSE was 22 and the highest 29 points, consistent with the level of education of people. As for the domicile of participants, 38% were from municipalities surrounding the stroke center. On the Rankin scale, at the time of discharge, 38% of individuals had a score of 1, while 30%, 23% and 7% scored 2, 3 and 4, respectively. After 90 days of the event, 76% of the participants scored 1. As for the nature of the transitions, it was evidenced by the change from health condition to disease, characterized as a transition of type health/disease, according to the Meleis' Theory, Initially, awareness of the new condition and current needs. For this, there is commitment through different efforts to live the transitional change. The time of transition is more pronounced after experiencing the acute phase of the disease, from hospital discharge in the home. This period is traversed in a different way by each of the people, in which events and critical points affect with greater or lesser depth in this trajectory. Also, it was evidenced conditioning factors that facilitate the transition, such as family support and assistance, and inhibitors such as the difficulty of access to rehabilitation and follow-up of the health team. Process indicators are associated with the evolution in rehabilitation stages, while the return to work and leisure activities can be constituted as result indicators. The transition experience of a stroke is unique for each person, who must be involved in the treatment and rehabilitation process, as well as needs the support of family members, services and multidisciplinary health team in monitoring this trajectory.